URGENSI PEMBENTUKAN PENDIDIKAN KARAKTER DI KALANGAN PELAJAR SMP MUHAMMADIYAH WAIPARE - Yuliana Mazing; Mariana Boleng; Maria Eugenia Yohtres Siga (LPPM Universitas Muhammadiyah Bulukumba, 2023)
This study aims to determine the urgency of forming character education for students at SMP Muhammadiyah Waipare. The problem in this study is that there are still many students who have poor character in speaking,not respecting fellow friends,and pitting one another against each other. This problem is due to the unfaorable character of the students. So that researhers are interested in conducting research related to “The urgency of forming character education among students of Muhammadiyah Waipare middle scholl. The research method used is a qualitative method. The data collection technique in this study is using observation intereview techniques and documentarise. In this research, the data sources were students at junior high school at SMP Muhammadiyah Waipare. The results of the study show that the urgency of forming character education for SMP Muhammadiyah Waipare students includes being : religious,honest,tolerant,disciplined, hard work,creative,independent,curious,national spirit,care for the environment,and responsibility.